Financial Development, Financial Market, and Financial Institutional on International Trade in Developing Eight Countries - Fajriyatul Abadiyah; Hikmah Endraswati (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2023)
This study aims to analyze the effect of financial development, financial market, and financial institutional on international trade in developing eight countries, with foreign exchange reserves, foreign direct investment, and real gross domestic product as control variables. This research includes descriptive quantitative research. The population used is eight developing countries. The data in this study is secondary data sourced from World Bank and International Monetary Fund (IMF) reports observation period from 2011 to 2020. The research model uses the panel data regression analysis method (Ordinary Least Square) through the Eviews 10 program. The results show that financial development has a positive and significant effect on international trade in D-8 countries, while financial markets and financial institutional have a significant negative effect on international trade in D-8 countries.